Who dares wins? : Do higher realistic occupational aspirations improve the chances of migrants for access to dual vocational education and training in Germany? - Beicht, Ursula [Verfasser]; Walden, Günter [Verfasser] (My University, 2019)
"High educational aspirations are considered to be a crucial factor for educational success and social advancement. As is also the case in many western European countries, migrants in Germany have higher aspirations than non-migrants. Although migrants' average school performance levels are significantly lower, their greater educational aspirations exert a positive influence on the acquisition of higher educational qualifications. This paper investigates whether higher aspirations are also revealed in respect of Germany's highly prevalent dual vocational education and training (VET) system and how this affects the transition to dual VET for young people from a migration background. Multivariate analyses using the database of the German National Educational Panel Study (NEPS) relate to school-leavers in Years 9 and 10 of general schools who aspired to enter dual VET upon completion of schooling. If we control for the main influencing factors, young people from a migrant background are shown to exhibit higher occupational aspirations with regard to dual VET than their counterparts not from a migration background. However, viewed in overall terms, higher occupational aspirations lead to poorer chances of transition to dual VET. This is much more noticeable amongst migrants than amongst non-migrants." (Authors' abstract, BIBB-Doku)
Keywords: P 1.5 Migranten; P 1.1 Jugendliche; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; Migrant; Ausländischer Jugendlicher; Schulabgänger; Berufseinmündung; Erste Schwelle; Bildungsaspirationen; Empirische Untersuchung; Multivariate Analyse; Nationales Bildungspanel